2018
DOI: 10.3389/fchem.2018.00430
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of α-In2Se3 Monolayer via Adsorption of Small Molecule for Gas Sensing

Abstract: Based on first-principles calculations, the adsorption of NO and NO2 gas molecules on the α-In2Se3 monolayer have been studied. The adsorption configuration, adsorption energy, electronic structure and charge transfer properties are investigated. It is found that the charge transfer processes of NO and NO2 adsorbed on the surface of α-In2Se3 monolayer exhibit electron donor and acceptor characteristics, respectively. After the adsorption of the molecules, the α-In2Se3 monolayers have new states near the Fermi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The N-O bond length was found to be 1.23 Å with a reduced angle of 127.72 • compared to 133.08 • for the detached molecule. We observed an interlayer distance of 2.97 Å with an adsorption energy of -0.190 eV alike the case on α-In 2 Se 340 and InSe 51. Continuing to the next case, we found that NO molecule favours adsorption at the centre of the hexagonal ring (T HR ) with a bond length of 1.15 Å.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…The N-O bond length was found to be 1.23 Å with a reduced angle of 127.72 • compared to 133.08 • for the detached molecule. We observed an interlayer distance of 2.97 Å with an adsorption energy of -0.190 eV alike the case on α-In 2 Se 340 and InSe 51. Continuing to the next case, we found that NO molecule favours adsorption at the centre of the hexagonal ring (T HR ) with a bond length of 1.15 Å.…”
supporting
confidence: 67%
“…In 2 Se 3 40 our obtained adsorption energies are adequately large to inhibit room-temperature thermal fluctuations (see Table 1) especially in the case of NO 2 on α-In 2 Se 3 where a weak physisorption energy of -0.058 eV was reported. In addition, our adsorption energy for NO and NO 2 molecules is indicative of a better adsorption/desorption recovery process on β-In 2 Se 3 as compared to the existing adsorption case on α-In 2 Se 3 .…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Adsorption phenomena have numerous industrial and environmental applications, such as desalination, cooling, wastewater treatment, gas or heat storage, and air purification (Burhan et al, 2016a , 2017 , 2018a , 2019a , 2020 ; Xie et al, 2018 ; Oh et al, 2019 ; Shahzad et al, 2019a , b ; Zhao et al, 2020 ). Such processes involve distinct interaction of adsorbate molecules over the porous surface of adsorbent material.…”
Section: Introductionmentioning
confidence: 99%